European Community--Sugar : Cross-Subsidization And The World Trade Organization - Hoekman, Bernard M. 1959- (The World Bank, 2007)
An important recent World Trade Organization dispute settlement case for many developing countries concerned European Union exports of sugar. Brazil, Thailand, and Australia alleged that the exports have substantially exceeded permitted levels as established by European Union commitments in the WTO. This case had major implications for both European Union sugar producers and developing countries that benefited from preferential access to the European Union market. It was also noteworthy in the use of economic arguments by the WTO dispute settlement panel, which held that the excess sugar exports were in part a reflection of illegal de facto cross-subsidization-rents from production that benefited from high support prices being used to cover losses associated with exports of sugar to the world market. Although in principle the economic arguments of the panel could apply to many other policy areas, in practice WTO provisions greatly limit the scope to bring similar arguments for trade in products that are not subject to explicit export subsidy reduction commitments of the type that were made for sugar and other agricultural commodities